Factors influencing person-centred care: Speech-language pathologists and audiologists perspective - Faheema Mahomed-Asmail; Louise Metcalfe; Marien A. Graham; Renata Eccles (African Journal of Disability)
Background: Person-centred care (PCC) is a fundamental aspect of healthcare, and its implementation is primarily based on clinicians’ initiation and sustained efforts and the availability of resources. Recent PCC literature has primarily focused on high-income settings, raising concerns about the feasibility of PCC implementation in low- and middle-income countries.